A Refunctionalisation of Form. The Modernist Turn in the Opus of Painter Leonid Šejka - Milosavljević-Ault, Angelina (Poznańskie Studia Slawistyczne, 2017)
Works by Belgrade artist Leonid Šejka (1932–1970) are usually considered fantastic, an embodiment of aesthetic ideals of Mediala Art Group he was a member of, an opposition to everything that Modernism stood for with its harsh formalism that expelled object. However, the complexity of Šejka’s opus as artist and theorist allows a different approach. In this paper, we turn to – so far neglected – Šejka‘s positive relation to Modernism, which he saw as a foundation for new aesthetic ideals. He understood that Modernism turned paintings into objects of empty forms void of function. Nevertheless, the future of painting, for him, resided in re-introduction of objects into painting in order to re-establish the necessary form-function relation, preserving, at the same time, Modernist traits. Šejka tried to demonstrate this in his mature works. He wrote about it in a series of writings, which contribute to our understanding of his opus.